2006
DOI: 10.1086/507955
|View full text |Cite
|
Sign up to set email alerts
|

PlanetPol: A Very High Sensitivity Polarimeter

Abstract: ABSTRACT.We have built and used on several occasions an optical broadband stellar polarimeter, PlanetPol, which employs photoelastic modulators and avalanche photodiodes and achieves a photon-noise-limited sensitivity of at least 1 in 10 6 in fractional polarization. Observations of a number of polarized standards taken from the literature show that the accuracy of polarization measurements is ∼1%. We have developed a method for accurately measuring the polarization of altitude-azimuth mounted telescopes by ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
118
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 122 publications
(121 citation statements)
references
References 30 publications
3
118
0
Order By: Relevance
“…The observations were carried out from 27 April 2005 to 8 May 2005 with a new high-sensitivity astronomical polarimeter PlanetPol, which achieves fractional polarization sensitivities better than 10 −6 with an absolute accuracy of about 1% (Hough et al, 2006). The polarimeter was mounted on the William Herschel Telescope located on the island of La Palma at an altitude of 2340 m. The measurements extended over a broad band of wavelengths from 590 to 1000 nm and were of polarized flux from four nearby stars which normally show little polarization.…”
Section: Polarimetry Observationsmentioning
confidence: 99%
“…The observations were carried out from 27 April 2005 to 8 May 2005 with a new high-sensitivity astronomical polarimeter PlanetPol, which achieves fractional polarization sensitivities better than 10 −6 with an absolute accuracy of about 1% (Hough et al, 2006). The polarimeter was mounted on the William Herschel Telescope located on the island of La Palma at an altitude of 2340 m. The measurements extended over a broad band of wavelengths from 590 to 1000 nm and were of polarized flux from four nearby stars which normally show little polarization.…”
Section: Polarimetry Observationsmentioning
confidence: 99%
“…As projects grow in scope and complexity, real error analysis and tradeoff studies are becoming essential as exemplified by the VLT and E-ELT codes under development (de Juan Ovelar et al 2011. Even axially symmetric telescope beams require calibration of instrumental polarization from the instrument optics and nonuniformities in coatings (Hough et al 2006;Bailey et al 2010Bailey et al , 2008Wiktorowicz & Matthews 2008) In the solar community, several instruments have included very fast polarimetric modulation to overcome many of these common instrument issues to achieve 0.001% differential precision polarimetry. Modulators include liquid crystals (LCs), piezo-elastic modulators (PEMs), rapidly rotating components and other techniques (Gandorfer 1999;Elmore et al 1992;Skumanich et al 1997;Gandorfer et al 2004;Lin et al 2004).…”
Section: Spectropolarimetric Instruments Errors and Suppression Tecmentioning
confidence: 99%
“…Modulation can be chromatically balanced, tuned or optimized for various observing cases (Povel 1995;Gisler et al 2003;Tomczyk et al 2010;de Wijn et al 2010de Wijn et al , 2011Snik et al 2009;López Ariste & Semel 2011;Nagaraju et al 2007). At modulation rates faster than 1kHz most instrument effects and even atmospheric seeing fluctuations can be suppressed (Keller et al 1994;Stenflo 2007;Hough et al 2006;Hanaoka 2004;Rodenhuis et al 2012;Xu et al 2006). Night-time modulation frequencies are usually much slower and fixed at the exposure time so that detector read noise does not dominate.…”
Section: Spectropolarimetric Instruments Errors and Suppression Tecmentioning
confidence: 99%
“…These results can be achieved thanks to radial velocity measurements, orbital brightness modulations, gravitational microlensing, direct imaging, astrometry, and polarimetry. The later is probably one of the most delicate methods since the anticipated white light polarization degree (about 10 −5 , Carciofi & Magalhães 2005;Kostogryz et al 2014;Kopparla et al 2016) resulting from scattering of stellar photons onto the atmospheric layers of Hot frederic.marin@astro.unistra.fr 1 In December 2016, 2695 planets out of a total of 3547 have been discovered by transit techniques, see http://exoplanet.eu/ Jupiters is expected to be just about detectable given the current limits of current optical, broad-band, stellar polarimeters (Schmid et al 2005;Hough et al 2006;Wiktorowicz 2009). Berdyugina et al (2008Berdyugina et al ( , 2011 reported to have successfully achieved a B-band polarimetric detection of HD 189733b and found a peak polarization of 2×10 −4 (i.e.…”
Section: Introductionmentioning
confidence: 99%